Seasonal variation of antioxidant capacity, phenols, minerals and essential oil components of sage, spearmint and sideritis plants grown at different altitudes - Chrysargyris, Antonios; Evangelides, Efstathios; Tzortzakis, Nikos G. (My University, 2021)
Medicinal and aromatic plants are well appreciated for their antioxidant and biocidal activ-ities, while great variation on these activities can be related to the species, environmental conditions and harvesting period. In the present study, the seasonal variation of the antioxidant activity, mineral content, yield and chemical composition of the essential oils (EOs) of sage (Salvia officinalis L.), sideri-tis (Sideritis perfoliata L. subsp. perfoliata) and spearmint (Mentha spicata L.) were tested under two different environmental conditions, each with a different altitude (namely mountainous and plain). Season affected total phenolic content and antioxidant capacity with increased values during winter and lower values during summer period. In summer, plants accumulated more Fe and had higher EO yield, while P and Na were accumulated more in winter. Altitude had a lesser effect on antioxidant capacity of the plants; however, increased minerals (N, K, Na and Ca) accumulation was found in plain areas. Sage plants had the highest antioxidant capacity, Zn content and EO yield. Sideritis had increased Fe content and spearmint plants revealed high N, Na and Mg levels. Furthermore, altitude and season had an impact on the content of main EOs components in all species. FRAP and ABTS were variably correlated with total phenols and minerals, depending on the species, season and altitude. In few cases, antioxidant activity was found to be inversely linked to some EO components (e.g., α-thujone in sage). Finally, the antioxidant content, minerals and EO yield and composition of the examined MAPs were all altered by season and altitude. These findings can be utilized to implement sage, sideritis and spearmint farming in specific ecosystems, determining the season and areas for harvesting the plants, in order to produce high-value products.
Keywords: ABTS; Altitude; Antioxidant status; FRAP; Season; Total phenols; Volatile compounds